Bibliometric Studies and Public Administration Research Potential on Stunting Problems - Trio Saputra; Sulaiman Zuhdi; Aguswan Aguswan; Reno Affrian; Eka Eka; Wasiah Sufi; Juraida Roito Harahap (Universitas Padjadjaran, 2023)
Stunting is an urgent issue that must be addressed immediately because it will affect the quality of Indonesia's human resources in the future. Human resources are the essential factor that determines the success of a country. This research aims to examine the development of stunting research in 2017-2022. Bibliometrics helps communicate discipline developments for other research purposes. This research aims to map the development of stunting research in 2017-2022. The findings of this study can be a starting point for further research on stunting. The research method employed was quasi-qualitative and bibliometric analysis. The research data is from articles from Google Scholar metadata for 2017-2022. The keyword